Synthesis of (benzimidazol-2-yl)aniline derivatives as glycogen phosphorylase inhibitors. Issue 21 (1st November 2016) - Galal, Shadia A.; Khattab, Muhammad; Andreadaki, Fotini; Chrysina, Evangelia D.; Praly, Jean-Pierre; Ragab, Fatma A.F.; El Diwani, Hoda I.
Graphical abstract: Abstract: A series of (benzimidazol-2-yl)-aniline (1 ) derivatives has been synthesized and evaluated as glycogen phosphorylase (GP) inhibitors. Kinetics studies revealed that compounds displaying a lateral heterocyclic residue with several heteroatoms (series 3 and 5) exhibited modest inhibitory properties with IC50 values in the 400–600 μM range. Arylsulfonyl derivatives7 (Ar: phenyl) and9 (Ar: o -nitrophenyl) of1 exhibited the highest activity (series 2) among the studied compounds (IC50 324 μM and 357 μM, respectively) with stronger effect than the p -tolyl analogue8 .